2005
DOI: 10.1177/1089313x0500900102
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Training for Dancers

Abstract: Dance performance has been classified as high-intensity intermittent exercise that utilizes the aerobic and glycolytic energy production systems. Dance class and rehearsal have been shown to inadequately stress these energy systems and supplemental training is one method of preparing the body to meet these demands. The use of interval exercise training to elicit the required training effect has been suggested and the recommended exercise-to-rest ratios are examined in relation to the underlying physiology. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The suggested WTR in dance classes has been suggested to be 1:3. 13 The time dancing can also be expressed as a percentage of the total time of the dance class or performance. Previous video analysis studies have found an average dancing time of 62.19 ± 13.91% for ballet performances and 68.97 ± 15.78% for contemporary dance performances.…”
Section: Introductionmentioning
confidence: 99%
“…The suggested WTR in dance classes has been suggested to be 1:3. 13 The time dancing can also be expressed as a percentage of the total time of the dance class or performance. Previous video analysis studies have found an average dancing time of 62.19 ± 13.91% for ballet performances and 68.97 ± 15.78% for contemporary dance performances.…”
Section: Introductionmentioning
confidence: 99%
“…The formal dance class has long been considered the cornerstone of training, providing all the technical, physical, and aesthetic requirements of dance [4]. As Matthew stated, the physiological demands of dance are considered high-intensity, intermittent, or interval in nature, involving both aerobic and anaerobic energy production systems [5]. Therefore, a dancer must be able to execute movements perfectly and possess solid endurance.…”
Section: Introductionmentioning
confidence: 99%